Delivery systems: A systematic approach for barrier management. (January 2020) - Li, Yuling; Guldenmund, Frank W.; Aneziris, Olga N.
Highlights: Barriers are classified for the purpose of safety management. Management tasks for barriers are identified and modelled. Delivery systems deliver suitable controls and resources to complete barriers. The link between delivery systems and barriers is further developed. The quantification of the competence delivery system helps developing the approach to safety management modelling. Abstract: Safety Management Systems usually follow specified formats, as required by standards and other procedures. The quality of such systems is often obtained with assessments at the ordinal measurement level. This paper introduces a barrier-based safety management system coupled with a quantitative approach to safety management modelling. The risk management part of this system is composed of so-called delivery systems, which describe the management processes in place in order to manage barriers. The proposed approach aims to determine how the delivered management factors affect risks by influencing the functioning of barriers. Taking the competence delivery system as an example, competent people are delivered to carry out the tasks of barriers, and these tasks guarantee barriers' effectiveness. In this research, barriers are grouped into five types. By quantifying competence indicators and the performance of each type of barrier, the link between a delivery system (competence) and barriers is established. Other delivery systems can be quantified in a similar way, meaning that safety management systems will work more efficiently with such monitoring. In addition, this quantification can be used as input for audits, by making assessments more transparent.